Invincible [videorecording (DVD)] - Core, Ericson; Wahlberg, Mark, 1971-; Kinnear, Greg, 1963-; Banks, Elizabeth, 1974- (Walt Disney Home Entertainment : Distributed by Buena Vista Home Entertainment, 2006)
Vince Papale is a down-on-his-luck substitute teacher in Philadelphia who, at the age of 30, was out of work, abandoned by his wife, and biding time as a part-time bartender when he decides to answer an open call for tryouts on the Philadelphia Eagles NFL football team in 1976. Going with his gut instinct, new coach Dick Vermeil rewards Papale's diligent efforts with a place on the team.